Ḵẖṳtbāt-i Āl Inḍiyā Sunnī Kānfarans, 1925 tā 1947 . (Maktabah-yi Ri̤zviyyah ; milne kā patā, Shirkat-i Ḥanafiyyah, 1978)
Collection of speeches delivered at various Sunni conferences held in undivided India between 1925 and 1947; includes a study of the contributions made to the Pakistan movement by Sunni religious leaders.